A Statistical Review of European Carriers’ Flight Delays and the Assessment of Delay Factors - Windusari, A.A. Ayu Diah; Pasaribu, Hisar Manongam (Warta Penelitian Perhubungan, 2023)
Disruption is an inherent risk that might arise because of the complexity and dynamic nature of air transport operations. In the aviation business, disruption can happen for a variety of reasons, including poor weather, strikes, and political factors. This study aims to analyse flight delays that European airlines encounter and assess the dependencies between different operation parameters through correspondence analysis in contingency tables that are visually represented using correspondence maps. This study examined data from selected European airlines between 2018 and 2022, which contained information on the length of delay, the reasons associated with it, and the specific characteristics of each flight, such as the type of flight, the type of aircraft, and the scheduled departure time. The result showed that even though there was a large decrease in the overall number of flights operated during the pandemic period in 2020 and 2021, the percentage of delayed flights still varies above 55%. Long-haul flights and larger aircraft tend to have longer delays. Except for 2020 and 2021, the percentage of delayed flights for different lengths of delays and scheduled departure times did not significantly change across the review years. The evaluation reason for delay appeared to increase with time due to airport or authority restrictions, while there was a tendency for the number of delayed flights related to technical aircraft, equipment, and ground operations to decrease. By developing an analysis of the root causes of flight delays using case studies that have already been published by different researchers and determining the degree to which an operating parameter contributes, we may provide guidelines for future studies that will uncover ways to minimize flight delays.